2019
DOI: 10.1111/abac.12179
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Expert Judgement: Analyzing Emerging Topics in Accounting and Finance Research in the Asia–Pacific

Abstract: In this paper, we focus on the question to what extent machine learning (ML) tools can be used to support systematic literature reviews. We apply a ML approach for topic detection to analyze emerging topics in the literature-our context is accounting and finance research in the Asia-Pacific region. To evaluate the robustness of the approach, we compare findings from the automated ML approach with the results from a manual analysis of the literature. The automated approach uses a keyword algorithm detection mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 103 publications
0
34
0
2
Order By: Relevance
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
“…According to that formula (1) all the values from data set (see table 4), in this case values (total number of words per category) derived from each article, were added up and then divided to the number of articles within the one-year range. In this way data from articles within the range of 2017 (3 articles) [11][12][13] 2018 (5 articles) [14][15][16][17][18], 2019 (4 articles) [19][20][21][22] and 2020 (4 articles) [23][24][25][26] are analyzed separately from the rest publishing years. See table 3.…”
Section: Algorithm Of Counting Wordsmentioning
confidence: 99%
“…To implement the burst detection algorithm, we used the Python library called burst_detection (Version 0.1.3). The parameters used were the resolution of state jumps set to 2 and the gamma set to 0.5 (see Cai et al ., 2019, for further explanation of these parameters). Topics had to appear at least five times to be considered for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Cai et al . (2019) already examined emerging trends in 11 accounting and finance journals (including 597 articles published in Accounting & Finance ) between 2009 and 2018. This study identified several emergent themes such as China‐related research, integrated reporting, as well as Fintech and environmentally focused research.…”
Section: Emerging Research Trends and Themesmentioning
confidence: 99%
“…The approach introduced here offers an improved approach to topic modeling. Topic modelling typically focuses on identifying a group of words (i.e., topic) from a collection of textual data [12][13][14], but has a number of limitations. In topic modelling, the user establishes the number of topics that will be extracted, which is based on an arbitrary selection [15].…”
Section: Mapping Academic Discoursesmentioning
confidence: 99%